Rietveld texture analysis from synchrotron diffraction images. I. Calibration and basic analysis. Issue 1 (23rd January 2014) - Lutterotti, Luca; Vasin, Roman; Wenk, Hans-Rudolf
<x content-type="archive" xml:space="preserve">Abstract</x> Synchrotron X-ray diffraction images are increasingly used to characterize not only structural and microstructural features of polycrystalline materials, but also crystal preferred orientation distributions. Diffraction data can be analyzed quantitatively and efficiently with the Rietveld method and here the detailed procedure is reported from the experiment to the calibration of the two-dimensional detector and full analysis of the sample. In particular, we emphasize the advantage of doing the calibration inside the Rietveld least-squares fitting instead of a preliminary graphical calibration. Then the procedure is described to quantify crystal preferred orientations with the Rietveld method implemented in software "Materials Analysis Using Diffraction". The process is illustrated for a US "nickel" coin, a 75 at.% copper 25 at.% nickel alloy with face-centered cubic structure and a strong cube texture.